PENGARUH KEPUASAN KERJA DAN IKLIM ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA PEGAWAI KPPBC TMP JUANDA - Anissatul Ghurriah (JURNAL PSIKOLOGI SKIsO (Sosial Klinis Industri Organisasi), 2020)
The purpose of this study was to determine and analyze the effect of job satisfaction and organizational climate on organizational citizenship behavior (OCB) in KPPBC TMP Juanda employees. This study uses a correlational quantitative method. To obtain data, questionnaires were distributed to 190 research samples. Sampling used saturated sampling technique. They are KPPBC TMP Juanda employees. The collected data were analyzed using multiple regression analysis techniques. The results of this study indicate that job satisfaction contributes an influence of 18.72%. Meanwhile, the contribution of organizational climate to OCB was 23.08%. The conclusions resulting from this study are: (1) job satisfaction has a positive effect on OCB (2) organizational climate has a positive effect on OCB (3) job satisfaction and organizational climate have a positive effect on OCB of KPPBC TMP Juanda employees. Keywords: Organizational Citizenship Behavior (OCB), Job Satisfaction, Organizational Climate